Mapping alternative strategies for pure play foundry in the semiconductor industry. - Lim, Gia Gia. (2008)
With China’s recent entry into the WTO and the existence of a vibrant electronics industry in the Pearl River Delta region, we explored the possibilities of establishing a PPF in Shenzhen/Hong Kong. Our attempt was to re-look the PPF strategy in Shenzhen/Hong Kong from a larger perspective by seeing Hong Kong as an integral part of the PRD region.